2004
DOI: 10.1029/2002jc001724
|View full text |Cite
|
Sign up to set email alerts
|

Kuroshio intrusion and the circulation in the South China Sea

Abstract: The Princeton Ocean Model is used to study the circulation in the South China Sea (SCS) and its seasonal transition. Kuroshio enters (leaves) the SCS through the southern (northern) portion of the Luzon Strait. The annually averaged net volume flux through the Luzon Strait is ∼2 Sv into the SCS with seasonal reversals. The inflow season is from May to January with the maximum intrusion of Kuroshio water reaching the western SCS during fall in compensation of summertime surface offshore transport associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
187
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 269 publications
(203 citation statements)
references
References 24 publications
9
187
0
Order By: Relevance
“…During winter northeast monsoon, along the northern boundary, the warm and saline Kuroshio Current water with oligotrophic properties intrudes through Luzon Strait and flows westward along the continental margin of China to become the deep-water mass of the nSCS (Nitani, 1972;Shaw, 1991). The coastal water of the East China Sea flows southwestward through Taiwan Strait into the nSCS (Fang et al, 1998;Xue et al, 2004). On the contrary, during the summer southwest monsoon, the Guangdong Coastal Current flows eastward along the southern coast of mainland China, which eventually flows into the East China Sea through Taiwan Strait.…”
Section: Introductionmentioning
confidence: 99%
“…During winter northeast monsoon, along the northern boundary, the warm and saline Kuroshio Current water with oligotrophic properties intrudes through Luzon Strait and flows westward along the continental margin of China to become the deep-water mass of the nSCS (Nitani, 1972;Shaw, 1991). The coastal water of the East China Sea flows southwestward through Taiwan Strait into the nSCS (Fang et al, 1998;Xue et al, 2004). On the contrary, during the summer southwest monsoon, the Guangdong Coastal Current flows eastward along the southern coast of mainland China, which eventually flows into the East China Sea through Taiwan Strait.…”
Section: Introductionmentioning
confidence: 99%
“…During autumn the maximum Kuroshio water intrusion reached the western SCS (Xue et al 2004). After entering the SCS the Kuroshio intrusion splits into three parts: a major part flows out of the SCS through the northern section of the Luzon Strait, the second part, known as the SCS Branch of Kuroshio (SCSBK) that occurs in autumn, flows southwestward along the 1000-m isobaths.…”
Section: Current Systems Effects On Sea-surface Chl-a Concentrationmentioning
confidence: 99%
“…Most of the complex surface currents are elongated parallel or sub-parallel to the continental margins (Shao et al 2004), among which is a consistent northeastward current named the South China Sea Warm Current (Guan 1978). This current straddles the shelf break region (Guan 1978;Hsueh and Zhong 2004;Xue et al 2004). Zhu et al (2010) suggested that this northeastwarddirected intermediate current has consistently existed at least from the middle Miocene to the present in the study area, and forced the canyons to migrate to the northeast during highstand periods.…”
Section: Structural Controlsmentioning
confidence: 99%
“…According to previous studies, the ocean current system in the northern South China Sea is complex owing to the combined influence of monsoon-driven surface currents and the South China Branch of Kuroshio current (Su 2004;Xue et al 2004;Shao et al 2004). Most of the complex surface currents are elongated parallel or sub-parallel to the continental margins (Shao et al 2004), among which is a consistent northeastward current named the South China Sea Warm Current (Guan 1978).…”
Section: Structural Controlsmentioning
confidence: 99%